Appearance‐based trust processing in schizophrenia. (6th September 2019) - Sutherland, Clare A. M.; Rhodes, Gillian; Williams, Nikolas; Connaughton, Emily; Ewing, Louise; Caruana, Nathan; Langdon, Robyn
Abstract : Objectives: Schizophrenia is characterized by impaired social interactions and altered trust. In the general population, trust is often based on facial appearance, with limited validity but enormous social consequences. The aim was to examine trust processing in schizophrenia and specifically to examine how people with schizophrenia use facial appearance as well as actual partner fairness to guide trusting decisions. Design: An experimental economic game study. Methods: Here, we tested how patients with schizophrenia and control participants (each N  = 24) use facial trustworthiness appearance and partner fairness behaviour to guide decisions in a multi‐round Trust Game. In the Trust Game, participants lent money to 'partners' whose facial appearance was either untrustworthy or trustworthy, and who either played fairly or unfairly. Clinical symptoms were measured as well as explicit trustworthiness impressions. Results: Overall, the patients with schizophrenia showed unimpaired explicit facial trustworthiness impressions and unimpaired facial appearance biases in the Trust Game. Crucially, patients and controls significantly differed so that the patients with schizophrenia did not learn to discriminate in the Trust Game based on actual partner fairness, unlike control participants. Conclusion: A failure to discriminate trust has important implications for everyday functioning in schizophrenia, as forming accurate trustworthiness beliefs is an essential social skill. Critically, without relying on more valid trust cues, people with schizophrenia may be especially susceptible to the misleading effect of appearance when making trusting decisions. Practitioner points: Findings People with schizophrenia made very similar facial trustworthiness impressions to healthy controls and also used facial appearance to guide trust decisions similarly to controls. However, the patient group were less able to explicitly distinguish between fair and unfair partners based on their behaviour compared with the control group. Moreover, people with schizophrenia failed to use actual partner fairness to guide their financial decisions in the Trust Game, unlike controls, and this impairment was specific to a social task. People with schizophrenia may be particularly reliant on facial appearance when trusting others, as they may struggle to incorporate more valid trustworthiness information in their decision‐making, such as actual partner fairness.